Rectal Tumour Staging with Endorectal Ultrasound: Is There Any Difference between Western and Eastern European Countries? - Anna Fábián; Renáta Bor; Klaudia Farkas; Anita Bálint; Ágnes Milassin; Mariann Rutka; László Tiszlavicz; Tibor Wittmann; Ferenc Nagy; Tamás Molnár; Zoltán Szepes (Gastroenterology Research and Practice)
Background. Rectal tumour management depends highly on locoregional extension. Rectal endoscopic ultrasound (ERUS) is a good alternative to computed tomography and magnetic resonance imaging. However, in Hungary only a small amount of rectal tumours is examined with ERUS. Methods. Our retrospective study (2006–2012) evaluates the diagnostic accuracy of ERUS and compares the results, the first data from Central Europe, with those from Western Europe. The effect of neoadjuvant therapy, rectal probe type, and investigator’s experience were also assessed. Results. 311 of the 647 ERUS assessed locoregional extension. Histological comparison was available in 177 cases: 67 patients underwent surgery alone; 110 received neoadjuvant chemoradiotherapy (CRT); ERUS preceded CRT in 77 and followed it in 33 patients. T-staging was accurate in 72% of primarily operated patients. N-staging was less accurate (62%). CRT impaired staging accuracy (64% and 59% for T- and N-staging). Rigid probes were more accurate (79%). At least 30 examinations are needed to master the technique. Conclusions. The sensitivity of ERUS complies with the literature. ERUS is easy to learn and more accurate in early stages but unnecessary for restaging after CRT. Staging accuracy is similar in Western and Central Europe, although the number of examinations should be increased.